2010
DOI: 10.1186/1479-5876-8-90
|View full text |Cite
|
Sign up to set email alerts
|

Three-day dendritic cells for vaccine development: Antigen uptake, processing and presentation

Abstract: BackgroundAntigen-loaded dendritic cells (DC) are capable of priming naïve T cells and therefore represent an attractive adjuvant for vaccine development in anti-tumor immunotherapy. Numerous protocols have been described to date using different maturation cocktails and time periods for the induction of mature DC (mDC) in vitro. For clinical application, the use of mDC that can be generated in only three days saves on the costs of cytokines needed for large scale vaccine cell production and provides a method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 37 publications
6
46
1
Order By: Relevance
“…The extensive culture period (7-9 days) of ex vivogenerated DCs and compounds required to differentiate them into DCs might negatively affect DC function, for example, by reducing proinflammatory cytokine production. Therefore, shorter culture protocols have been developed (11). Furthermore, natural DCs do not require extensive culture, and recently, it has been proven feasible to obtain more than 10 million pDCs and even higher numbers of BDCA-1 þ mDCs after a single leukapheresis despite their low frequency in blood (12)(13)(14).…”
Section: Vaccinesmentioning
confidence: 99%
“…The extensive culture period (7-9 days) of ex vivogenerated DCs and compounds required to differentiate them into DCs might negatively affect DC function, for example, by reducing proinflammatory cytokine production. Therefore, shorter culture protocols have been developed (11). Furthermore, natural DCs do not require extensive culture, and recently, it has been proven feasible to obtain more than 10 million pDCs and even higher numbers of BDCA-1 þ mDCs after a single leukapheresis despite their low frequency in blood (12)(13)(14).…”
Section: Vaccinesmentioning
confidence: 99%
“…Given their involvement in virtually any immune process, PBMC isolation is a key step in many immunological experiments. Once isolated, PBMCs can be used for a wide range of downstream applications such as studying autoimmune diseases [1][2][3], cancer research [4][5][6][7][8][9][10], developing new vaccines [11][12][13] and immunotherapies [6][7][8][9][10], drug discovery and testing [14][15][16] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of studies concluded that fDCs are as good as their conventional counterparts [12,14e18], there is no strong evidence confirming that the fast DC protocol is efficient enough to undergo clinical trials. Namely, it has been reported that fDCs could have a weaker antigen uptake [15,16], antigen presentation and costimulation [14,16] and higher IL-10 production on stimulation with a TLR7/8 agonist [17]. Similarly, we showed previously that DCs generated by the fDC protocol mature poorly in the presence of proinflammatory cocktail, unlike their conventional counterparts [18].…”
Section: Discussionmentioning
confidence: 68%
“…The majority of studies comparing the conventional and fast protocol suggested that fast DCs (fDCs) are as good as their conventional counterparts [12,14e17]. However, different data showing that fDCs have a weaker antigen uptake [15,16], weaker antigen presentation and co-stimulation [14,16] and a higher IL-10 production on stimulation [17] point to their weaker potential in a clinical setting for antitumor therapy. In line with this, our previous data [18] suggest that the conventional protocol for the generation of DCs is more reliable than the fast DC protocol because the monocytes of all examined donors cultivated by standard methods had good potential to differentiate into mature, IL12eproducing DCs.…”
Section: Introductionmentioning
confidence: 98%